2015
DOI: 10.1016/j.clinph.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Event related potentials study of aberrations in voice control mechanisms in adults with attention deficit hyperactivity disorder

Abstract: Objective The present study was designed to test for neural signs of impulsivity related to voice motor control in young adults with ADHD and healthy control young adults using EEG recordings in a voice pitch perturbation paradigm. Methods Two age-matched groups of young adults were presented with brief pitch shifts of auditory feedback during vocalization. Compensatory behavioral and corresponding bioelectrical brain responses were elicited by the pitch-shifted voice feedback. Results The analysis of bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
(90 reference statements)
2
7
0
Order By: Relevance
“…The main behavioral result of our study replicates findings from other studies (Behroozmand & Larson, 2011; Hawco, et al, 2009; Korzyukov, et al, 2015; Scheerer, et al, 2013) demonstrating that when the F0 magnitude of feedback perturbations is greater than 250 cents, vocal response magnitudes decreased (Scheerer, et al, 2013). Taken together the results of the present and previous studies strongly suggest that feedback perturbations larger than 250–300 cents are perceived as not self-generated but as an acoustical change in the environment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main behavioral result of our study replicates findings from other studies (Behroozmand & Larson, 2011; Hawco, et al, 2009; Korzyukov, et al, 2015; Scheerer, et al, 2013) demonstrating that when the F0 magnitude of feedback perturbations is greater than 250 cents, vocal response magnitudes decreased (Scheerer, et al, 2013). Taken together the results of the present and previous studies strongly suggest that feedback perturbations larger than 250–300 cents are perceived as not self-generated but as an acoustical change in the environment.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that bioelectrical brain responses to 400 cents stimuli predominantly reflected auditory sensory activity rather than motor activity (for more details see: Korzyukov, et al, 2015) and SoA. As can be seen from the grand-averaged ERP data in Figure 3, the patterns of the P50-N1-P2 ERP responses for the 400 cents ”Up” and “Down” shifts were similar to the waveforms reported in conventional auditory ERP studies (Burkard, et al, 2007).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, both the BAP(+) and BAP(−) parent groups exhibited decreased response onset latencies compared to parent controls, and the ASD group showed a similar trend, though this failed to reach significance. This response pattern may be reflective of impulsivity in neural control of speech (e.g., as previously identified in children and adults with attention‐deficit/hyperactivity disorder [ADHD; Korzyukov et al, ]. Indeed, behavioral manifestations of impulsivity have also been noted in parents of individuals with ASD, particularly those with the BAP, in the form of increased social disinhibition [Landa et al, ; Murphy et al, ; Wolff, Narayan, & Moyes, ].…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, several studies have identified significant overlap between ADHD and ASD such that approximately half of individuals with ASD exhibit difficulties with ADHD‐related behaviors, including impulsivity [Goldstein & Schwebach, ; Yoshida & Uchiyama, ]. As Korzyukov et al [] suggested for individuals with ADHD, atypicalities in inhibitory mechanisms may be related to differences in involuntary motor control of the voice in individuals with ASD and their parents. Given that the pattern of impulsivity was not specific to the BAP but rather observed in the ASD parent group overall, decreased response latencies to PPAF during speech (unlike increased response magnitudes to PPAF during the sustained vowel production) may reflect more general liability to neurodevelopmental disorders, including ADHD and language‐related disorders, rather than ASD specifically.…”
Section: Discussionmentioning
confidence: 99%